EF hand-mediated Ca2+- signalling in photoreceptor synaptic terminals - Schmitz, Frank; Natarajan, Sivaraman; Venkatesan, Jagadeesh K.; Wahl, Silke; Schwarz, Karin; Grabner, Chad P. (Frontiers in Molecular Neuroscience, 2012)
Photoreceptors, the light-sensitive receptor neurons of the retina, receive and transmit a plethora of visual informations from the surrounding world. Photoreceptors capture light and convert this energy into electrical signals that are conveyed to the inner retina. For synaptic communication with the inner retina, photoreceptors make large active zones that are marked by synaptic ribbons. These unique synapses support continuous vesicle exocytosis that is modulated by light-induced, graded changes of membrane potential. Synaptic transmission can be adjusted in an activity-dependent manner, and the synaptic ribbons, Ca2+- and cGMP-dependent processes appear to play a central role. EF-hand-containing proteins mediate many of these Ca2+- and cGMP-dependent functions. Since continuous signalling of photoreceptors appears to be prone to malfunction, disturbances of Ca2+- and cGMP-mediated signalling in photoreceptors can lead to visual defects, retinal degeneration and even blindness. This review summarizes aspects of signal transmission at the photoreceptor presynaptic terminals that involve EF-hand-containing Ca2+-binding proteins.